New Insights Into the Paleoseismic History of the Mae Hong Son Fault, Northern Thailand - Chansom, Chanista; Jitmahantakul, Sukonmeth; Owen, Lewis A.; Wiwegwin, Weerachat; Charusiri, Punya (Frontiers in Earth Science, 2022)
The Mae Hong Son Fault (MHSF) is a north-trending active fault in northern Thailand. The largest earthquake ever recorded in Thailand occurred in February 1975 with a magnitude of 5.6 and was associated with the southern end of the MHSF. Paleoearthquake magnitudes, recurrence intervals, and slip rates for the MHSF are evaluated using the morphological characteristics of the MHSF aided with a 12.5-m-resolution digital elevation model (DEM) and using fault trenching. Morphotectonic analysis, including studies of offset streams, linear valleys, triangular facets, and fault scarps helps illustrate dextral fault movements within the MHSF zone. Two separated N-S trending basins, the Mae Hong Son to the north and the Mae Sariang to the south, are present along the MHSF. Between these basins, fault displacements decrease towards the Khun Yuam area. Surface rupture length investigation from fault segments in both basins indicates maximum credible earthquake magnitudes of between 5.8 and 6.3. Fault trenching and road-cut studies show that nine earthquakes occurred along the MHSF over the past ~43 ka. Optically stimulated luminescence (OSL) dating help define the timing of the earthquakes to ~43, ~38, ~33, ~28, ~23, ~18, ~13, ~8, and ~3 ka. The recurrence interval of earthquakes on the Mae Hong Son Fault is ~5,000 years and the fault has a slip rate of ~0.04–0.15 mm/a.